Guía de conservación para las ranas pristimantis allpapuyu y pristimantis hampatusami especies endémicas de la provincia de El Oro - Flores Castillo, Gloria Elizabeth (My University, 2021)
Ecuador is a country with great biodiversity, a small example is the province of El Oro where it is home to several species of amphibians including Pristimantis allpapuyu and Pristimantis hampatusami, the same that were found in the Buenaventura Ecological Reserve and Catamayo-Alamor. The objective of the research is to create a conservation guide with which people can apply measures that help conserve the ecosystems where these amphibians live and learn about the benefits they have. The research has a methodology based on a qualitative approach in which certain techniques were applied such as literature review using books, scientific articles, repositories, among others. The results obtained in the project are that the biological diversity that exists motivates people to commit many acts against nature, ignoring national and international laws that protect it. Among the activities that are carried out is mentioned the illegal trafficking of wildlife, which generates millions of dollars a year, although it is not left behind that the deterioration of the habitat also causes the loss of species. In conclusion, this guide can be useful for people to have knowledge about the contributions that amphibians provide to nature and how they can help to recover the ecosystems of these species.
El Ecuador es un país con gran biodiversidad, un pequeño ejemplo, es la provincia de El Oro donde es el hogar de varias especies de anfibios entre ellas la Pristimantis allpapuyu y Pristimantis hampatusami, las mismas que fueron encontradas en la Reserva Ecológica Buenaventura y en Catamayo-Alamor. El objetivo de la investigación es realizar una guía de conservación con la cual las personas puedan aplicar medidas que ayudan a conservar los ecosistemas donde habitan estos anfibios y conocer los beneficios que estos tienen. La investigación tiene una metodología que se basa en un enfoque cualitativo en la cual se aplicaron ciertas técnicas como la revisión de la literatura utilizando libros, artículos científicos, repositorios, entre otros. Los resultados obtenidos en el proyecto es que es la diversidad biológica que existe motiva a cometer muchos actos en contra de la naturaleza pasando por alto las leyes nacionales e internación que la protegen, entre las actividades que se realizan se menciona al tráfico ilegal de vida silvestre, la cual genera millones de dólares al año, aunque no se deja atrás que el deterioro del hábitat también provoca la pérdida de especies. En conclusión, esta guía puede servir para que las personas tengan conocimiento sobre los aportes que brindan los anfibios a la naturaleza y como pueden ayudar para recuperar los ecosistemas de estas especies.
Keywords: ANFIBIO; BIODIVERSIDAD; COMERCIO ILEGAL; MEDIO AMBIENTE